2024
DOI: 10.1039/d3mh01496g
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and cold-tolerant moisture-enabled power generator combining ionic diode and ionic hydrogel

Jiahao Fang,
Xiang Zhang,
Peng Duan
et al.

Abstract: Ionic hydrogel is combined with ionic diode structure to prepare a moisture-based power generator, demonstrating an excellent balance of high output power and high freeze resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In addition, it has been proved that adding more movable protons to an MEG can increase the current output. 18,26,52 In our experiments, seawater was employed to produce the electric power, and it was found that seawater can significantly increase the current output without affecting its voltage due to the salt in the water. The peak current can reach 37.65 μA (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, it has been proved that adding more movable protons to an MEG can increase the current output. 18,26,52 In our experiments, seawater was employed to produce the electric power, and it was found that seawater can significantly increase the current output without affecting its voltage due to the salt in the water. The peak current can reach 37.65 μA (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…A variety of new materials and microstructures, such as hydrogels, 21,22 two-dimensional materials, 23–25 and polymer materials, 26–29 have been used to construct ionic gradients or specialized channels to drive the MEGs. Currently, polymers containing specific functional groups ( e.g.…”
mentioning
confidence: 99%